Anti-viral immune enhancer properties of some micro-nutrients and functional Herbs with the potential to augment the treatment of COVID-19 patients - yaseen galali; Simon Davies; Holem Balaky; Ahmad Jabbar (مجلة جامعة الانبار للعلوم الصرفة)
The world is currently experiencing a severe acute respiratory system challenge in 2021, which is a global pandemic caused by COVID-19 and is killing thousands of people worldwide. With having no particular vaccine and/or medical treatment and increased mortality over time consequently threatening community health and economics, urgent and accessible alternative strategies to mitigate this disease are required. Based on earlier studies on other coronavirus family members like MERS and SARs CoV, this review summarizes the potential use of particular micronutrients and herbs to lower risks, decrease the mortality rate, and/or treat current COVID-19. The authors conducted an online search using the terms MERS, SARS, and respiratory tract infection viruses in order to achieve that goal. The results of the systematic study showed that several nutrients including vitamin; D, A, E, C, B complex, zinc, selenium, Iron, and herbs such as garlic, black seed and licorice can be used as urgent supporting agents that can improve immune system and help mitigate against COVID-19. In conclusion, to control the COVID-19 outbreak, it has been suggested that all feasible measures, including preventative and prophylactic measures as well as community nutrition status, should be taken into account